EDUKASI DAN PELATIHAN PEMANTAUAN PERTUMBUHAN BALITA BAGI IBU SEBAGAI UPAYA DETEKSI DINI STUNTING DI NEGERI TULEHU KABUPATEN MALUKU TENGAH - Santi Aprilian Lestaluhu; Nilfar Ruaida; Nurhayat Rustam (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service is to provide education and training to mothers to detect early stunting in Tulehu Country. The Implementation Method consists of Preparation, Education and Training, Assistance in Posyandu activities, and Activity Monitoring. The results of the activity showed that there was an increase in mothers' knowledge after education and training. After education and training conducted direct monitoring and evaluation at the posyandu, the results showed increased mothers' knowledge in measuring and weighing toddlers' weight using anthropometry. In conclusion, there is an increase in the ability of mothers to detect stunting.